1996
DOI: 10.1046/j.1365-2133.1996.d01-1104.x
|View full text |Cite
|
Sign up to set email alerts
|

A new method of intralesional bleomycin therapy in the treatment of recalcitrant warts

Abstract: We have used a new technique of bleomycin injection to treat intractable palmar, plantar and periungual warts. Following local anaesthesia with topical EMLA (lignocaine and prilocaine) cream, 1 mg/ml bleomycin solution was dropped on to the wart and 'pricked' into the wart using a Monolet needle. We achieved 92% success rate which compares well with other authors whose success rates with intralesional bleomycin vary between 33 and 92%. We conclude that this technique of intralesional bleomycin therapy is an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 12 publications
2
63
0
1
Order By: Relevance
“…Thus, their average duration approaches the mean duration of spontaneous cure. The clearance rate of 87.88% achieved in the present study is similar to that of previous reports using bleomycin [3,4,6,7,8,9,10]. While the pharmacological mechanism of pingyangmycin for wart treatment remains to be revealed, we assume that it has clinical effects similar to bleomycin as pingyangmycin is a member of the bleomycin reagent family [11].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, their average duration approaches the mean duration of spontaneous cure. The clearance rate of 87.88% achieved in the present study is similar to that of previous reports using bleomycin [3,4,6,7,8,9,10]. While the pharmacological mechanism of pingyangmycin for wart treatment remains to be revealed, we assume that it has clinical effects similar to bleomycin as pingyangmycin is a member of the bleomycin reagent family [11].…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have demonstrated that bleomycin is effective in over two thirds of wart cases [3,4]. The exact mechanism of bleomycin is yet unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in a 92% clearance rate. 182 Others have used modified tattooing devices with some success. 172 Five randomized, controlled trials have evaluated the effectiveness of bleomycin; 102 however, it is difficult to compare the trials.…”
Section: Antimitotic Therapymentioning
confidence: 99%
“…This obvious response to treatment makes it difficult to conduct double-blinded trials, and many studies have been open studies or have used bleomycin in comparison with saline injection or cryotherapy. Open studies have suggested clearance rates of approximately 20-90% of treated warts with one or more treatments, 101,102 with most reporting a patient response rate of approximately 65-85%. 101,103 Several trials of intralesional bleomycin have used saline as a placebo.…”
mentioning
confidence: 99%